Traditional Medicines Derived from Domestic Animals Used by Rebari Community of Rajasthan, India - Vyas, N.; Mahawar, M.M.; Jaroli, D.P. (Our Nature, 2010)
This Paper deals with the domestic animals based traditional medicinal knowledge of Rebari community of Rajasthan. Field study was conducted with Rebari people with the help of semi-structured questionnaire and open interview. 25 Rebari people including both sexes provided valuable information regarding uses of domestic animals and their products in local medicinal system and information was obtained, about their conservation too. The results show that there are 15 domestic animals and 2 plant species used in 30 ailments like headache, tuberculosis, paralysis and anal infection. The Rebari community has devised rules to ensure the social and ecological sustainability of their livestock but presently, these domestic animals are on verge of extinction due to the shortage of grazing land and loss of their territories. So there is an urgent need to uphold livestock diversity for appropriate medicinal use and to maintain an ecological balance in nature. Key words: Rebari community, traditional medicine, livestock conservation, Rajasthan DOI: 10.3126/on.v7i1.2560 Our Nature (2009) 7:129-138